Students' satisfaction towards academic advising service / Azianti Ismail ... [et al.] - Ismail, Azianti; Roslan, Liyana; Ismail, Herda Balqis; Mohd Salleh, Noor Azlina (Universiti Teknologi MARA, 2021)
Effective academic advising service has been found to bring positive benefits to educational institutions to increase students' retention rates and graduation. This study sought to find the essential attributes in public university academic advising service in UiTM Pasir Gudang campus, Malaysia, which may be used to improve the service provided to the students. Quantitative research was conducted using a questionnaire adapted from Parasuraman's SERVQUAL model with a sample size of 221. The study aimed to examine the relationship between service quality dimensions and students' satisfaction. Descriptive statistics, correlation, and multiple regression analysis were used to analyse the questionnaires. Multiple regression analyses results showed reliability and empathy were two dimensions that had significant relationship with students' satisfaction. The results also demonstrated a statistical difference in academic advising service satisfaction among the students according to their years of study and meeting frequency with advisors. The findings of this study may be valuable for the institution to understand the factors that are most significant to further improve the students' satisfaction level in academic advising service.